Elimination therapy for the endemic malarias. - Baird, J (2012)
Most malaria diagnosed outside endemic zones occurs in patients experiencing the consequences of what was likely a single infectious bite by an anopheline mosquito. A single species of parasite is nearly always involved and expert opinion on malaria chemotherapy uniformly prescribes species- and stage-specific treatments. However the vast majority of people experiencing malaria, those resident in endemic zones, do so repeatedly and very often with the involvement of two or more species and stages of parasite. Silent forms of these infections-asymptomatic and beyond the reach of diagnostics-may accumulate to form substantial and unchallenged reservoirs of infection. In such settings treating only the species and stage of malaria revealed by diagnosis and not others may not be sensible or appropriate. Developing therapeutic strategies that address all species and stages independently of diagnostic evidence may substantially improve the effectiveness of the control and elimination of endemic malaria.